Professionality Analysis of Basic Education Teachers As Agents To Improve Creativity in Digital Era - Iskandar, Rossi; MS, Zulela (Universitas Pendidikan Ganesha, 2021)
A teacher possesses low competency, so that reform is needed that can increase a teacher's creativity. This study aimed to analyze the competence, creativity, and professionalism of primary education teachers as reform agents and optimize basic education teachers' strategies in the digital era. This research is a type of library research (library research). The subject of this research is the competence of basic education teachers. The data collection method used is a literature study. The data analysis technique of this research is qualitative data analysis techniques. The results show that the professional competence of basic education teachers as agents of reform is the ability to master materials, structures, concepts, and scientific mindsets that support the subjects being taught and the ability to utilize information and communication technology (ICT) in supporting learning and professional development through reflective action. So it can be concluded that efforts to drive better change in the world of education prioritize improving teacher quality. It is necessary to have creative and quality teachers to bring about changes and innovations both academically and non-academically. The implication of this research is to add insight into the basic competencies of a basic education teacher.